PENGARUH PERPUTARAN KAS DAN PERPUTARAN PIUTANG TERHADAP PROFITABILITAS PERUSAHAAN SUB-SEKTOR FOOD AND BEVERAGES TAHUN 2012-2016 - Nuriyani, Nuriyani; Zannati, Rachma (Economic Faculty, Attahiriyah Islamic University, 2017)
The objective of this research is to determine the effect of cash turnover and receivable turnover to profitability (ROA). Data used in this study were secondary data from financial statements in Indonesia Stock Exchange in the year of 2012 to 2016 of a food and beverage manufacturing company. Independent variables in this research are cash turnover and receivable turnover, while the dependent variable in this study is profitability. The analysis method used is multiple linear regression, determination coefficient test (R2), F test and T-test. The result of these analyses showed that profitability was influenced simultaneously by cash turnover and receivable turnover. While on partial analysis showed only cash has significant influence to profitability. Keywords: Cash Turnover, Accounts Receivable Turnover, Profitability